Preliminary validity and reliability evidence of the Brief Antisocial Behavior Scale (B-ABS) in young adults from four countries - Mezquita, Laura (2021)
The present research built on the Self-Reported Delinquency interview and the Antisocial Behavior Scale to develop an updated brief instrument to measure antisocial behavior. College students (n = 3188, 67.75% women) from the USA, Argentina, the Netherlands and Spain completed an online survey. Analyses that combined approaches from the Classical Test Theory and Item Response Theory were conducted to select the items for the brief version. Findings suggested that a 13-item Brief Antisocial Behavior Scale (B-ABS) fulfilled the high-quality criteria: salient factor loadings, adequate discrimination, variability in response endorsement, adequate fit based on infit/outfit values, nondifferent item functioning across the four participating countries, and Cronbach?s alpha and ordinal omega coefficients higher than .70. The B-ABS scores generally significantly correlated with personality scores, mental health and marijuana outcomes, showing criterion-related validity evidence. Our overall findings suggest that B-ABS adequately assesses antisocial behavior in young adults from different countries/cultures.